Developing English language teachers' and learners' ELF awareness: the background, design, and impact of the ENRICH project's continuous professional development programme. - Nicos Sifakis; Yasemin Bayyurt; Lili Cavalheiro; Maria Fountana; Lucilla Lopriore; Dina Tsagari; Stefania Kordia (Journal of English as a Lingua Franca, 2022)
The paper presents the background, design, implementation and impact of the Continuous Professional Development (CPD) programme of the EU-funded ENRICH Project, which ran from 2018 to 2021. The programme, which has been freely available online since January 2022 (http://enrichproject.eu), aims at implementing the principles and processes of ELF awareness in empowering English language teachers to integrate the role of English as a Lingua Franca in their multilingual classrooms. We begin by justifying the development of the ENRICH Project with reference to the policies of the European Union supporting multilingualism and go on to discuss the principles of ELF awareness that informed the ENRICH CPD programme. We also present the priorities, target groups, key objectives and innovative practices of the ENRICH CPD programme. The paper is rounded up with a sample of participants’ responses to certain CPD activities and with an appreciation of the impact of the programme on participant teachers and their learners.